A Truthful Mechanism for Scheduling Delay-Constrained Wireless Transmissions in IoT-Based Healthcare Networks - Yi, Changyan; Cai, Jun (IEEE transactions on wireless communications, 2019)
In this paper, the scheduling management of delay-constrained medical packet transmissions in Internet of Things (IoT)-based healthcare networks is studied. Unlike most existing works in the literature, we focus on beyond wireless body area network (beyond-WBAN) communications, i.e., data transmissions between smart WBAN-gateways (e.g., smartphones) and the base station (BS) of remote medical centers. In our model, various medical packets are randomly aggregated at each gateway (which ordinarily stands for one patient), and their delay-constrained beyond-WBAN transmission requests are immediately reported to the network controller (i.e., BS) with different priority levels reflecting their medical importance. The BS schedules the uplink beyond-WBAN transmissions by forming a queueing system which addresses specific medical-grade quality of service requirements, including the priority awareness and the delay constraints of medical packet transmissions. By taking into account the natural device intelligence of smart gateways in IoT-based networks, we design a truthful and efficient mechanism which can prevent gateways from strategically misreporting the priority levels of medical packets, while incentivizing the BS to manage the transmission scheduling according to the desired manner. Both theoretical and simulation results examine the feasibility of the proposed mechanism and demonstrate its superiority over the counterparts.